Analytical Method to Improve the Security of Internet of Things with Limited Resources - Hannan Khan, Abdul; Yamin Siddiqui, Shahan; Sohail Irshad, Muhammad; Ali, Saif; Rehan Saleem, Muhammad; Iqbal, Shahid (EAI Endorsed Transactions on Internet of Things, 2019)
This research is about the information security of very obliged gadgets. Design Science Research (DSR) Method is utilized for this reason. It let us pick up the fundamental thought and exploration of the primary issue space. This is a procedure of combining distinctive pre-affirmed examines to pick up the goal. Symmetric cryptography will be utilized as a noteworthy device in various information items and entryway gadgets. The principle target of this exploration is to give security to exceptionally constrained gadgets as they are not ready to convey utilizing TLS or DTLS given a deficiency of assets. This arrangement is a finished bundle to give credibility, information honesty and privacy, either information is making a trip to entryway, gadgets or the web. At the information interface layer, AES symmetric encryption is utilized and information questions likewise are encoded utilizing a similar encryption strategy. Assessment is performed using wire shark.
Keywords: Internet of Things (IoT); Design Science Research (DSR); Advanced Encryption Standard (AES); Transport Layer Security (TLS); Datagram Transport Layer Security (DTLS)